SURGICAL TREATMENT OF HIASOPHAGEAL HERNIAS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Unlike traditional methods, which focus primarily on mechanical suturing of the hernia defect, the developed approach takes into account the severity of axial displacement, cardia geometry, the state of the antireflux valve mechanism, and esophageal motility, allowing for the development of a personalized surgical strategy.